Meta-analisis: efektivitas model pembelajaran kreatif terhadap hasil belajar biologi siswa sma di sulawesi - Kurnianti, Pelasari; Saleh, Andi Rahmat (Universitas Tanjungpura, 2023)
The education quality index of a region is inseparable from the quality of human resources occupying that region. Quality human resources are obtained from quality education and quality education will be achieved when the learning process is carried out effectively and efficiently. Learning is said to be effective and efficient when it provides learning outcomes above the specified standards. This requires a creative learning model. Research with the title effectiveness of creative learning models on biology learning outcomes for high school students in Sulawesi, is based on the aim of knowing how much influence the application of creative learning models has on biology subjects at the senior high school level on the island of Sulawesi. The research was carried out by applying the method of meta-analysis using 7 articles from Indonesian journals as research subjects. Based on the research, it was found that the creative learning model was effective or had a positive influence when applied at the XI high school level. If, in terms of the type of creative learning model used, the PBL type has the greatest influence on student learning outcomes and when viewed from the subject matter of the subject matter, creative learning model is most effectively applied to digestive system material